A mouse model for X-linked adrenoleukodystrophy - Lu, Jyh-Feng (The National Academy of Sciences of the USA, 1997)
X-linked adrenoleukodystrophy (X-ALD) is a peroxisomal disorder with impaired β-oxidation of very long chain fatty acids (VLCFAs) and reduced function of peroxisomal very long chain fatty acyl-CoA synthetase (VLCS) that leads to severe and progressive neurological disability. The X-ALD gene, identified by positional cloning, encodes a peroxisomal membrane protein (adrenoleukodystrophy protein; ALDP) that belongs to the ATP binding cassette transporter protein superfamily. Mutational analyses and functional studies of the X-ALD gene confirm that it and not VLCS is the gene responsible for X-ALD. Its role in the β-oxidation of VLCFAs and its effect on the function of VLCS are unclear. The complex pathology of X-ALD and the extreme variability of its clinical phenotypes are also unexplained. To facilitate understanding of X-ALD pathophysiology, we developed an X-ALD mouse model by gene targeting. The X-ALD mouse exhibits reduced β-oxidation of VLCFAs, resulting in significantly elevated levels of saturated VLCFAs in total lipids from all tissues measured and in cholesterol esters from adrenal glands. Lipid cleft inclusions were observed in adrenocortical cells of X-ALD mice under the electron microscope. No neurological involvement has been detected in X-ALD mice up to 6 months. We conclude that X-ALD mice exhibit biochemical defects equivalent to those found in human X-ALD and thus provide an experimental system for testing therapeutic intervention.